Urgency of Socialization Regarding Regulation of Village Head Election in Prasung Village, Buduran District, Sidoarjo - adhitya widya kartika (Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
Abstract The rule of law and democracy carries the consequence that the actions of the government in administering the government system must be in accordance with or limited to laws and regulations and include the community as well as in the village government system. Democracy is manifested in the implementation of village head elections. Election of Village Heads is different from general elections (in general) this is seen from several things. In addition there is the dynamics of legislation related to the election of village heads so the government and the community are bound and obey the laws and regulations. Therefore it is important if the village government and the village community understand the regulation, so socialization is needed so that the same understanding occurs. Likewise with the election of village heads inVillage Prasung, Buduran District, Sidoarjo Regency, East Java Province should be in accordance with the laws and regulations that have been enacted. However, there is a dispute related to the statutory provisions governing the election of village heads, namely the prohibition of candidates who are sentenced to imprisonment based on a court decision that has the legal force fixed for a minimum of 5 (five) years or more to nominate as a candidate for village head. However, there are exceptions when completed and announced in connection with the conviction. Therefore, there are several results of the analysis that then arise, among others, it is correct that the organizer of the election of the village head if the implementation of compliance with applicable regulations, there is less explicit meaning of the exclusion in the terms of the prohibition of the convicted or after serving a crime. Keywords: Socialization, Village Head Election, Rule of Law, Democracy, Village